Effects of elevated arsenic and nitrate concentrations on groundwater resources in deltaic region of Sundarban Ramsar site, Indo-Bangladesh region. (March 2023) - Biswas, Tanmoy; Pal, Subodh Chandra; Chowdhuri, Indrajit; Ruidas, Dipankar; Saha, Asish; Islam, Abu Reza Md. Towfiqul; Shit, Manisa
Abstract: An attempt has been adopted to predict the As and NO3 − concentration in groundwater (GW) in fast-growing coastal Ramsar region in eastern India. This study is focused to evaluate the As and NO3 − vulnerable areas of coastal belts of the Indo-Bangladesh Ramsar site a hydro-geostrategic region of the world by using advanced ensemble ML techniques including NB-RF, NB-SVM and NB-Bagging. A total of 199 samples were collected from the entire study area for utilizing the 12 GWQ conditioning factors. The predicted results are certified that NB-Bagging the most suitable and preferable model in this current research. The vulnerability of As and NO3 − concentration shows that most of the areas are highly vulnerable to As and low to moderately vulnerable to NO3 . The reliable findings of this present study will help the management authorities and policymakers in taking preventive measures in reducing the vulnerability of water resources and corresponding health risks. Graphical abstract: Unlabelled Image Highlights: Most important factors influencing As and NO3 - concentration are Mg2, pH and depth. Sundarban islands regions have been identified as As and NO3 - pollution hotspot. NB-Bagging was the best model for achieving high prediction precision.